Foreign Labour Migration, Economic Growth and Remittances in Nepal - Kunwer, Laxman Singh (Patan Pragya, 2019)
This paper examines the history and current situation of foreign labour migration in Nepal, which is in increasing trend. This paper highlights on some major push and pull factors, impacts of labour migration and remittances. The role and impacts of remittances in Nepal are also another key issue of this paper. The objective of paper is to discuss historical aspects and highlights the role of remittances in Nepal. The paper is developed with the help of secondary sources of information and discussed only on Nepalese foreign labours. The existing exploitative working environment in destinations of Nepalese migrations labpurs, lack of skills and trainings among labour migrants including government to government agreement between labour sending (Nepal) and labour receiving countries to protect rights of labour migrants also has been discussed. This paper also highlights the need of effective foreign labour policies based on scientific research. There is need of reliable and proper environment of investment of remittances in productive sectors as well as use of migrant's skills and knowledge to achieve prosperity of nation.